(untitled) (Academia Science Repository, 2023)
The development of children’s patriotism, the need for education in preschoolers, their propensity for studying, regular preparation for the educational process, the development of children’s thinking, the development of their capacity for independent and free expression of their opinions, and the wellbeing of their physical and mental health. To ensure that, in the implementation of such tasks, the educator’s use of examples of folk art in his training will help the educational process to be more effective. In this article, there are thoughts and comments about the specific features of educating preschool children through folklore.